Selective activator protein‐1 inhibitor T‐5224 prevents lymph node metastasis in an oral cancer model. Issue 5 (26th April 2016) - Kamide, Daisuke; Yamashita, Taku; Araki, Koji; Tomifuji, Masayuki; Tanaka, Yuya; Tanaka, Shingo; Shiozawa, Shunichi; Shiotani, Akihiro
Abstract : Activator protein‐1 (AP‐1) is a transcriptional factor that regulates the expression of various genes associated with tumor invasion and migration. The purpose of our study was to assess the therapeutic effects of a novel selective AP‐1 inhibitor, T‐5224, in preventing lymph node metastasis in head and neck squamous cell carcinoma (HNSCC) in an orthotopic mouse model. We assessed the effect of T‐5224 on HNSCC cell invasion, migration, proliferation, and MMP activity by carrying out an in vitro study using an invasion assay, scratch assay, WST‐8 assay, and gelatin zymography. We also observed morphological changes in HNSCC cells by time‐lapse microscopy. Furthermore, cervical lymph node metastasis was assessed using an orthotopic tumor model of human oral squamous cell carcinoma cells (HSC‐3‐M3) injected in the tongue of a BALB/c nude mouse. T‐5224 (150 mg/kg) or vehicle was given orally every day for 4 weeks. Animals were killed and assessed for lymph node metastasis by H&E staining of resected lymph nodes. T‐5224 significantly inhibited the invasion, migration, and MMP activity of HNSCC cells in a dose‐dependent manner; there was no significant influence on cell proliferation. The antimetastatic effect of T‐5224 was also confirmed in our animal study. The rate of cervical lymph node metastasis in the model was 40.0% in the T‐5224‐treated group ( n = 30) versus 74.1% in the vehicle‐treated group ( n = 27; P < 0.05). In conclusion, T‐5224 inhibited the invasion and migration of HNSCC cells in vitro, and prevented lymph node metastasis in head and neck cancer in an animal model. Abstract : AP‐1 inhibitor T‐5224 prevents lymph node metastasis in head and neck cancer model.